An Analysis of Thematic Progression Pattern Found in Thesis Abstracts by Postgraduate English Education Students - Chyntia Latifah; Maulidiyyatul Uswah (Journal of Pedagogi, 2024)
This study investigates thematic progression patterns used in thesis abstracts written by postgraduate English education students. The fourth abstract thesis are analyzed the theme and rheme structured within for each clause then examined whether the types of thematic progression is used. In a short, it explores how themes are used and structured in written text. It examines the three types of thematic progression based on Brian Paltridge’s theory employed and analyzes their frequency. A qualitative research method employs to analyze, categorize, and understand the patterns of thematic progression. The findings showed that among the different thematic progression patterns used in abstracts, constant themes are the clear favorite (30%), followed by linear themes (12%) and split rheme (4.3%). In can be interpreted that the limited use of thematic progression patterns in the analyzed thesis abstracts indicates that some postgraduate English education students may need further guidance on constructing clear and concise abstracts. To enhance the coherence and readability of their abstracts, these students should be encouraged to employ thematic progression strategies more effectively.